Comparison of mechanical and ultrasonic agitation methods for mono c‐Si texturing. Issue 10 (3rd June 2016) - Bilgen, Sedat; Es, Firat; Turan, Rasit
Abstract : Texturing of a mono crystalline Si wafer aims to create light trapping structures to reduce the reflection losses. Being a cheap and efficient process, alkaline texturing of Si wafers is commonly used in all industrial mono crystalline solar cell production lines. However, standard process with potassium hydroxide (KOH)‐based solutions with isopropyl alcohol (IPA) addition suffers from instability, high material consumption, and nonuniformities in the shape and the distribution of the pyramid structures formed on the Si surface. In this work, we studied the effect of ultrasonic agitation (UA) during the etching process on the structural, optical, and electrical properties of mono crystalline Si solar cell as a function of process parameters. We have shown that UA improves optical and electrical performance of the cells by forming uniform pyramid structures. In addition, it also helps to lower the material consumption and Si removal from the surface by enabling less process time and temperature. Ultrasonic agitation of the etching solution proves to be a good modification of the wet process steps for the mono crystalline silicon solar cell technology.